Maternal Self-Critical and Dependent Personality Styles and Mother-Infant Communication. (June 2017) - Beebe, Beatrice; Lachmann, Frank
This study investigated mother-infant communication in relation to Blatt's measures of adult personality organization, namely, interpersonal relatedness and self-definition, defining the higher ends of these two measures as dependency and self-criticism, respectively. A nonclinical sample of 126 mother-infant dyads provided the data. An evaluation of maternal self-criticism and dependency was made six weeks postpartum; four months postpartum, mother-infant self- and interactive contingencies during face-to-face play were studied and analyzed in conjunction with the earlier evaluation. Self- and interactive contingencies were defined by the predictability within, and between, the behaviors of each partner. This approach assesses the process of relating from moment to moment within a dyad. Self-contingency measures the degree of stability/variability of one person's ongoing rhythms of behavior; interactive contingency measures the likelihood that one person's behavior is influenced by the behavior of the partner. Infant and mother facial affect, gaze, and touch, and infant vocal affect, were coded second by second from split-screen videotape. Maternal self-criticism and dependency had strikingly different effects on mother-infant communication. Self-critical mothers showed lowered attention and emotion coordination, staying more "separate" from infants in these realms, compromising infant interactive efficacy. This finding is consistent with Blatt and colleagues' descriptions of self-critical individuals as preoccupied with self-definition, compromising relatedness. Dependent mothers and their infants showed reciprocal emotional vigilance, consistent with Blatt and colleague's description of dependent individuals as "empty" and "needy" of emotional supplies from their partner. The study documents that the influence of the mother's personality organization operates through both infant and maternal contributions, a co-created process rather than a direct unilateral transmission from mother to infant.